Waqf and Sustainability: A Text Mining - Sukmana, Raditya; Rusydiana, Aam Slamet; Laila, Nisful (Management and Sustainability, 2023)
The purpose of this study was to conduct a bibliometric analysis of all publications on Scopus related to waqf and sustainability. The methodology for text mining was carried out in July 2021 by searching for all references related to the themes of "waqf" and "sustainability" in all fields of Scopus and 292 pieces of scientific literature were found. In addition, the results of this review include documents published from 2003 to 2021. The results show that the number of publications on the theme of waqf and sustainability continues to increase. The results showed that the most productive and growing journal was the Journal of Islamic Accounting and Business Research. The most popular authors are Hassan MK, Kassim S, Mohammed MO, and Umar UH, the most productive institution is Universiti Teknologi Mara, the most popular country is Malaysia, and the most popular keyword topics are investment, theoretical model, governance approach, and sustainable development. The number of Waqf articles in their role in sustainability continues to grow. This study also reviews the development of research on waqf trends and sustainability from various fields including citations, journals, countries, authors, institutions, to topics. The implication of this research is to identify the development of research trends in the theme of waqf and sustainability.